2017
DOI: 10.1519/jsc.0000000000001505
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Single Whole-Body Cryotherapy Exposure on Physiological, Performance, and Perceptual Responses of Professional Academy Soccer Players After Repeated Sprint Exercise

Abstract: Tables: 1 6 Cryotherapy and recovery from soccer 2 MANUSCRIPT TITLE:The effects of a single whole body cryotherapy exposure on physiological, performance and perceptual responses of professional academy soccer players following repeated sprint exercise RUNNING TITLE: Cryotherapy and recovery from soccerCryotherapy and recovery from soccer 3 ABSTRACT 7In professional youth soccer players, the physiological, performance and perceptual effects of a single 8 whole body cryotherapy (WBC) session performed shortl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
4
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 25 publications
3
42
4
7
Order By: Relevance
“…On the contrary, in a randomized, counterbalanced and crossover design, 14 habituated English Premier League academy soccer players, Russell and colleagues found that a single WBC session (−135°C, 2 min), performed within 20 min after a repeated sprint exercise (15 × 30 m), increased salivary testosterone, yet had no effect on cortisol, blood lactate, and CK nor on performance (peak power output), recovery, and soreness perceptions (Russell et al, 2017). …”
Section: Muscle Damage Parameters Fatigue Recovery and Painmentioning
confidence: 99%
“…On the contrary, in a randomized, counterbalanced and crossover design, 14 habituated English Premier League academy soccer players, Russell and colleagues found that a single WBC session (−135°C, 2 min), performed within 20 min after a repeated sprint exercise (15 × 30 m), increased salivary testosterone, yet had no effect on cortisol, blood lactate, and CK nor on performance (peak power output), recovery, and soreness perceptions (Russell et al, 2017). …”
Section: Muscle Damage Parameters Fatigue Recovery and Painmentioning
confidence: 99%
“…Several studies have investigated the physical, psychological, and physiological effects of WBC following exercise (for a review see [1,2,15]) Many [13,[16][17][18][19], but not all [20,21] have reported that WBC might facilitate the recovery process after exercise. Actually, for most biomarkers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürdeki çalışmalara bakıldığında, kriyoterapi uygulamasının tüm vücut veya lokal olarak uygulandığı gözlemlenmiştir. 2,22,23 Tüm vücut kriyoterapi uygulaması ile ilgili bir çalışmada fiziksel olarak aktif bireylerde kriyoterapi (3 dk boyunca -110°C sıcaklıkta sıvı azottan soğuk hava üretilmesi) ile kas yorgunluğu sonrası toparlanmaya bakılmıştır. 22 Başka bir çalışmada ise profesyonel futbolcularda tekrarlı sprint egzersizi sonrası tüm vücut kriyoterapinin (30 sn-60°C, 120 sn-135°C sıvı nitrojen bölmeleri) fizyolojik, performans ve algısal etkileri incelenmiştir.…”
Section: Discussionunclassified
“…22 Başka bir çalışmada ise profesyonel futbolcularda tekrarlı sprint egzersizi sonrası tüm vücut kriyoterapinin (30 sn-60°C, 120 sn-135°C sıvı nitrojen bölmeleri) fizyolojik, performans ve algısal etkileri incelenmiştir. 23 Değerlendirmeler alt ekstremitede yapılmıştır. Üst ekstremite için kriyoterapinin akut etkisinin değerlendirildiği çalışmalarda propriyosepsiyon, kas kuvveti ve atış doğruluğu incelenmiştir.…”
Section: Discussionunclassified